Предмет: Алгебра,
автор: capitanrex80
Преобразуйте в алгебраическую дробь рациональное выражение.
Заранее благодарю.
Приложения:
Ответы
Автор ответа:
0
= 2(х²+3х+9)-18х-(х-3)(х-3) / (х-3)(х²+3х+9) = 2х²+6х+18-18х-х²+6х-9 / (х-3)(х²+3х+9) = х²-6х+9 / (х-3)(х²+3х+9) = (х-3)² / (х-3)(х²+3х+9) = х-3 / х²+3х+9
а) х-3 / х²+3х+9 = 0-3 / 0²+3*0+9 = -3 / 9 = - 1/3
б) х-3 / х²+3х+9 = 3-3 / 3²+3*3+9 = 0
а) х-3 / х²+3х+9 = 0-3 / 0²+3*0+9 = -3 / 9 = - 1/3
б) х-3 / х²+3х+9 = 3-3 / 3²+3*3+9 = 0
Похожие вопросы
Предмет: Алгебра,
автор: saharuku
Предмет: Английский язык,
автор: hohol223
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: АЛЬБИНАКРОМВНЛЬ
Предмет: Биология,
автор: hawk1050